Decreased expression of LIF mRNA in patients withmyoma uteri. Issue 3 (22nd September 2018) - Kara, Mustafa; Sabah Ozcan, Seda; Aran, Turhan; Kara, Ozlem; Yilmaz, Neziha
Abstract: Objective: The aim of this study was to evaluate endometrial receptivity by measuring HOXA‐10, HOXA‐11, and LIF gene expressions in women with polycystic ovary syndrome. Methods: A total of 48 women were included in this clinical study. Thepatients were allocated to two groups: study group consisted of 28 patients with myoma uteri and control group consisted of 20 patients without myoma uteri. Endometrial sampling was performed during the proliferative phase. The biopsies obtained from the patients with myoma uteri were taken from the place where the fibroids were localized. HOXA‐10, HOXA‐11, and LIF expressions were measured in the endometrial sampling material. Demographic data of the patients such as age, obstetric and gynecologic history, medical conditions, medications, surgical history, last menstrual period were recorded. Also, the number, size, localization, and type of the myoma were registered. Results: The mean age of the patients was 42.07 and 38.17, respectively. HOXA‐11 levels in the study and control groups were 0.004 ± 0.001 and 0.010 ± 0.001, respectively ( P < 0.90). Paradoxically, HOXA‐10 levels were found to be higher in the study group than the control group, but the difference was not statistically significant ( P < 0.25). LIF levels were significantly lower in the study group ( P < 0.05). Conclusion: Our results showed that myoma uteri might lead to a decrease in implantation rate by diminishing LIF gene expressions. However, there were no differences between the two groups in terms of HOXA‐10 and HOXA‐11 levels. Abstract : We wanted to investigate the relationship between homeobox genes and LIF levels and myoma uteri